2021
DOI: 10.1123/japa.2020-0155
|View full text |Cite
|
Sign up to set email alerts
|

Tai Chi for the Prevention of Falls Among Older Adults: A Critical Analysis of the Evidence

Abstract: Despite interest as to the benefits of Tai Chi, there remains a controversy over its effectiveness as an exercise intervention for preventing falls among older adults. This review synthesizes the evidence base with a focus on meta-analyses and randomized controlled trials with community-dwelling older adults. It provides a critical lens on the evidence and quality of the trials. High-quality evidence suggests that Tai Chi is an effective intervention for preventing falls in community settings; however, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 64 publications
1
9
0
Order By: Relevance
“…However, although the efficacy of TC is clear in studies that a TC protocol compares to a control group [11,12,14] , in cases where its efficacy is compared to another method, its superiority over the other method is unclear [17,18] . The findings of this review are consistent with those of Nyman [19] , who also found in his review the lack of evidence about the efficacy of TC against other similar interventions in reducing falls in older adults.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, although the efficacy of TC is clear in studies that a TC protocol compares to a control group [11,12,14] , in cases where its efficacy is compared to another method, its superiority over the other method is unclear [17,18] . The findings of this review are consistent with those of Nyman [19] , who also found in his review the lack of evidence about the efficacy of TC against other similar interventions in reducing falls in older adults.…”
Section: Discussionsupporting
confidence: 90%
“…However, it is not clear whether personalized TC programs can improve adherence to exercise. According to Nyman [19] , 71-81% of community-dwelling older adults are adherent to class-based Tai Chi interventions. More research is therefore needed to provide more evidence on the efficacy between individualized or group programs.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, transfer to gait stability from solely standing balance training [ 4 6 ] is suggested by improved clinical balance scores, gait parameters, and performance on the timed up and go, and other tests. In addition, studies that trained standing balance found reduced falls [ 7 ]. Consequently, the existence of transfer from standing balance training to gait, as well as the mechanisms underlying such a transfer, if present, are insufficiently clear.…”
Section: Introductionmentioning
confidence: 99%
“…Song et al 's finding indicated that Tai Chi practice improved physical stability during the performance of dual tasks in older adults (Song et al, 2018). In comparison with other exercise interventions, Tai Chi might be a superior strategy for fall reduction through benefitting the cognitive function (Nyman, 2021) and neuromuscular function improvements (Hu et al, 2021). Yuan Yang et al randomly assigned 26 healthy older women to the Tai Chi group and Control group, with Tai Chi group performing Tai Chi exercise for 8 weeks and Control group engaging in daily activities, and after Tai Chi intervention, the Tai Chi group demonstrated elevated HbO 2 concentration in the PFC (Yang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%